Phase Equilibrium of CO2 Hydrate with Rubidium Chloride Aqueous Solution - Ryonosuke Kasai; Leo Kamiya; Ryo Ohmura (Separations)
Salt lakes are a rich source of metals used in various fields. Rubidium is found in small amounts in salt lakes, but extraction technology on an industrial scale has not been developed completely. Clathrate hydrates are crystalline compounds formed by the encapsulation of guest molecules in cage-like structures made of water molecules. One of the most important properties for engineering practices of hydrate-based technologies is the comprehension of the phase equilibrium conditions. Phase equilibrium conditions of CO2 hydrate in rubidium chloride aqueous solution with mass fractions of 0.05, 0.10, 0.15 and 0.20 were experimentally investigated in the pressure range from 1.27 MPa to 3.53 MPa, and the temperature was from 268.7 K to 280.6 K. The measured equilibrium temperature in this study decreased roughly in proportion to the concentration of the RbCl solution from the pure water system. This depression is due to the lowering of the chemical potential of water in the liquid phase by the dissolution of RbCl. Experimental results compared with other salt solution + CO2 hydrate systems showed that the equilibrium temperatures decreased to a similar degree for similar mole fractions.